Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Controls, Diagnostics and Instrumentation 2012
DOI: 10.1115/gt2012-68982
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic Computations of Contra-Rotating Open Rotors Using the Nonlinear Harmonic Method and a Chorochronic Approach

Abstract: Due to their great potential for fuel saving, Contra-Rotating Open Rotors (CRORs) receive renewed interest by the airframers and the engine manufacturers. The inherent high efficiency of this propulsion system, however, is potentially offset by the level of noise emitted by the open blades. The acoustic impact on passengers and community may represent a major issue to their environmental acceptance. Fast and robust noise prediction tools are clearly required to support the development of quieter propellers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…If the number of blades in each blade row match, β = 0 according to Eq. (15). In this special case, it is found that Eq.…”
Section: Iic Phase-shifted Periodic Boundary Conditionmentioning
confidence: 77%
See 2 more Smart Citations
“…If the number of blades in each blade row match, β = 0 according to Eq. (15). In this special case, it is found that Eq.…”
Section: Iic Phase-shifted Periodic Boundary Conditionmentioning
confidence: 77%
“…This information was used to set the phase shift according to Eq. (15). To ensure that the gusts were convected with the flow, i.e.…”
Section: Iid2 Cascade Gust Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…If coupling between the unsteady perturbations is to be accounted for, the nonlinear terms in the URANS equations must be retained in the analysis. A common approach in this case is to integrate the equations in time [8][9][10], possibly in combination with the Chorochronic method [11] which is used to reduce the computational domain to one blade per row. Although time accurate solutions generally are computationally expensive, this approach has the clear advantage of making few assumptions on the nature of the flow apart from the choice of turbulence modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Harmonic Balance method as well as similar methods have been employed for turbomachinery tonal noise predictions with good results, see e.g. [9,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%